AB0376 Neither RA Disease Activity nor TNFI Increase the Incidence of Lymphoma in A Large, US RA Registry. (10th June 2014) - Furst, D.E.; Cox, V.; Etzel, C.J.; Greenberg, J.D.; Collier, D.
Abstract : Background: The incidence of lymphoma is increased in patients with rheumatoid arthritis. There is controversy; however, regarding whether disease activity influences the incidence of lymphoma in this disease. Likewise, the effect of TNFi on the incidence of lymphomas in RA is unclear. We examined the effect of disease activity and the use of TNFi on the incidence of lymphomas in the CORRONA Registry. Methods: Patients: All RA CORRONA patients were included who: 1) were on a TNFi or non-biologic DMARD (nbDMARD) at time of enrollment, (2) had available clinical disease activity index (CDAI) at the time of enrollment and (3) had at least one follow-up visit. If a patient switched among treatment groups (nbDMARD to TNFi), then time within each drug group was accounted for in the analyses. Outcomes: The incidence of MD reported lymphomas was the primary outcome. Analysis: Average CDAI was calculated as the area under the curve (AUC) during the period of follow-up. Additional variables examined included: age, gender, education, smoking, BMI, disease duration, RF/CCP status, erosions, other nbDMARD use (among TNFi group), prednisone, comorbid conditions and family history of cancer/lymphoma. In addition to descriptive statistics, lymphoma incidence rate per 100 person years was calculated. The Kaplan-Meier method estimated time to first lymphoma and the proportion of lymphoma events after drug initiation. As sensitivity analysis we used modified DAS28 for the CDAI. Results: As of 3/4/13, 19, 608 RA patients met the study inclusion criteria: 7729 (37.8%) used TNFi and 11879 (58.1%) used nbDMARD start of follow-up period. TNFi users had more severe disease at baseline (erosions: 52.3% versus 41%; p<0.001). TNFi patients were slightly younger (56 versus 59 years, p<0.001) but had longer disease duration (11.0 versus 8.1 years, p<0.001), and prednisone use was slightly less (27% versus 31%, p<0.001). MD reported lymphomas were rare (67 lymphomas/60145 patient years=0.11/100 person years), resulting in very wide confidence intervals by disease activity (Table 1 ). Compared to nbDMARD the rate of incident lymphomas in TNFi users was 1.08 (0.93-1.25) using CDAI or mDAS (p=NS for both). Conclusions: In the CORRONA database of 19608 RA patients neither disease activity nor use of TNFi affected the incidence of lymphomas over 3.1 years. Acknowledgements: The CORRONA RA registry has been supported through contracted subscriptions in the last two years by Abbvie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Eli Lilly, Novartis, Pfizer, Vertex and UCB. Disclosure of Interest: D. Furst Grant/research support: AbbVie, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, BMS, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: Abbvie, Actelion, UCB (CME ONLY), V. Cox Employee of: CORRONA, Inc., C. Etzel Employee of: CORRONA, Inc., J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca, Pfizer, Employee of: CORRONA, Inc., D. Collier Shareholder of: Amgen, Employee of: Amgen DOI: 10.1136/annrheumdis-2014-eular.2064